Out of the Inferno : Poles Remember the Holocaust - Lukas, Richard C., 1937- (Book collections on Project MUSE., 1989)
"" Richard Lukas's book, encompassing the wartime recollections of sixty ""ordinary"" Poles under Nazi occupation, constitutes a valuable contribution to a new perspective on World War II. Lukas presents gripping first-person accounts of the years 1939-1945 by Polish Christians from diverse social and economic backgrounds. Their narratives, from both oral and written sources, contribute enormously to our understanding of the totality of the Holocaust. Many of those who speak in these pages attempted, often at extreme peril, to assist Jewish friends, neighbors, and even strangers who otherwi